Design and Implementation of PI and PID Controller for symmetrical multilevel boost Converter - El Haji Ikram; Mustapha Kchikach; Elhasnaoui Abdnnebi; Sahbani Sanaa (EPJ Web of Conferences, 2025)
In this research, we propose developing and executing PID and PI controllers for a symmetrical multilevel boost converter in Matlab/Simulink. The symmetrical multilevel converter is powered by a 15 V DC generator with a 50 kHz switching frequency. Simultaneously, the desired output voltage is 60 V. To study the converter's performance in closed loop mode, the output voltage signals are compared in open and closed loop modes. The results show that the PID and PI controllers increase the output voltage by 23.55 V with low voltage ripples and overshoot. In addition, the PI controller minimizes the rising time, whereas the PID controller reduces the settling time, steady-state error, voltage ripples, and transient voltage overshoot.